2022
DOI: 10.1038/s41598-022-17317-6
|View full text |Cite
|
Sign up to set email alerts
|

Selective electrochemical reduction of CO2 on compositionally variant bimetallic Cu–Zn electrocatalysts derived from scrap brass alloys

Abstract: The electrocatalytic reduction of carbon dioxide (CO2RR) into value-added fuels is a promising initiative to overcome the adverse effects of CO2 on climate change. Most electrocatalysts studied, however, overlook the harmful mining practices used to extract these catalysts in pursuit of achieving high-performance. Repurposing scrap metals to use as alternative electrocatalysts would thus hold high privilege even at the compromise of high performance. In this work, we demonstrated the repurposing of scrap brass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 73 publications
1
16
0
Order By: Relevance
“…Although it has a flexible capacity, e.g., it can also be used to do catalyst reconstructions with modified electrolyte compositions. Electrodes with recycled brass alloys with differing Zn contents were synthesized when performing CO 2 RR in gastight H-cell, which enables the transformation of CO 2 toward CO and formate . The scrap alloys were made more selective for CO generation through in situ galvanic replacement with Ag and activated toward the CO 2 RR by simple annealing in air.…”
Section: Engineering Of Electrolyzersmentioning
confidence: 99%
“…Although it has a flexible capacity, e.g., it can also be used to do catalyst reconstructions with modified electrolyte compositions. Electrodes with recycled brass alloys with differing Zn contents were synthesized when performing CO 2 RR in gastight H-cell, which enables the transformation of CO 2 toward CO and formate . The scrap alloys were made more selective for CO generation through in situ galvanic replacement with Ag and activated toward the CO 2 RR by simple annealing in air.…”
Section: Engineering Of Electrolyzersmentioning
confidence: 99%
“…This electrode exhibited high CO 2 electroreduction selectivity toward CO with 85% faradaic efficiency. Badaway and coworkers 163 showed that repurposing scrap brass alloys with different Zn content allowed for the conversion of CO 2 into carbon monoxide and formate. The selectivity towards CO formation was improved when the alloys were galvanically replaced with Ag.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…The electrocatalytic activity of the fabricated composites toward OER and HER in alkaline electrolyte (1 M KOH) was studied. In addition, density functional theory (DFT), a powerful tool that helps in understanding the properties of various materials and reaction mechanisms, was employed to elucidate the observed electrocatalytic activity of the materials for water splitting. ,, Moreover, the effect of incorporating P into the MnFeCoNi catalyst was fully investigated using both experimental measurements and DFT calculations.…”
Section: Introductionmentioning
confidence: 99%